Performance studies: An introduction - Schechner, Richard (New York Routledge, 2002)
In this second edition, the author opens with a discussion of important developments in the discipline. His closing chapter, 'Global and Intercultural Performance', is completely rewritten in light of the post-9/11 world. Fully revised chapters with new examples, biographies and source material provide a lively, easily accessible overview of the full range of performance for undergraduates at all levels in performance studies, theatre, performing arts and cultural studies. Among the topics discussed are the performing arts and popular entertainments, rituals, play and games as well as the performances of everyday life. Supporting examples and ideas are drawn from the social sciences, performing arts, post-structuralism, ritual theory, ethology, philosophy and aesthetics.User-friendly, with a special text design, Performance Studies: An Introduction also includes the following features:numerous extracts from primary sources giving alternative voices and viewpointsbiographies of key thinkersstudent activities to stimulate fieldwork, classroom exercises and discussionkey reading lists for each chaptertwenty line drawings and 202 photographs drawn from private and public collections around the world.